Struggling against the consequences of bioethanol production. Narratives of a local environmental justice movement in Córdoba, Argentina - Tittor , Anne (2020)
The production of bioenergy and especially of agrofuels is highly contested, both on a local and global scale. While most research has focused on rural areas and sustainability, our case study explores a conflict around bioethanol production within an urban context: the city of Córdoba, Argentina. Describing the emergence and narratives of a local protest movement within the neighbourhood next to the ethanol factory, our article aims to contribute to the debate on the externalities of bioenergy from an environmental justice perspective. The article shows that the struggle against bioethanol production in the neighbourhood emerged as a local environmental justice movement concerned about the uncertainties regarding health risks and the danger of explosions. At the start, the activists did not define themselves as ‘environmentalists’ or ‘ecologists’. This is not an environmentalism of choice, but an environmentalism ‘of obligation’, starting from their struggle to defend their bodies, health, lives and territory. The authorities ignored their claims, and so, facing sociotechnical controversies, the movement invested huge efforts into critical epidemiology and created alliances with health and science professionals and institutions. Through their struggle, they developed their own narrative, questioning the enterprise’s narrative of ‘green’ and ‘sustainable’ energy. The movement fully developed its own understanding of environmental justice in unison with other environmental and human rights movements in the country.